Research on natural disaster emergency monitoring system. (7th April 2020) - Yang, Jianliang; Hou, Hanping; Geng, Shaoqing; Qiao, Shaobo; Wang, Yue; Tang, Fangcheng; Wang, Xuan
Monitoring is the main emergency information and intelligence department. The natural disaster emergency rescue decision is made on the basis of disaster monitoring information. Obtaining timely and accurate disaster information is the fundamental guarantee for emergency and rapid rescue. Based on the research status of natural disaster emergency monitoring system, this paper proposes the establishment of sky-ground integrated natural disaster emergency monitoring system based on the research method of system management theory, and analyses quantitatively the system performance. Finally, it points out the operation mode and guarantee of the system. The mechanism provides reference for the construction of a scientific and perfect natural disaster emergency monitoring system, which really shortens the time of 'black box' and 'grey box', solves the 'vacuum' of rescue and realises rapid rescue.